Neglected vector-borne bacterial diseases and arboviruses in the Mediterranean area. (November 2018) - Charrel, R.N.; Berenger, J.-M.; Laroche, M.; Ayhan, N.; Bitam, I.; Delaunay, P.; Parola, P.
Abstract: Arthropod vectors can transmit pathogenic microorganisms from one vertebrate to another during their blood meal. Although some vector-borne diseases have been eradicated in the Mediterranean area, such as malaria and dengue, recent endemic microorganisms (Toscana virus, Rickettsia spp.) remain neglected even though they cause many more cases. New diagnostic tools and innovative tools for the identification and characterization of vector species and microorganisms have been developed at IHU Méditerranée Infection, either internally or through collaborative and integrated projects. We have detected Rickettsia slovaca as a human pathogen and have described the disease; we have shown that Rickettsia felis can be transmitted by Anopheles mosquitoes; we have emphasized the increasing importance of bedbug ( Cimex lectularius ) as a potential vector of Bartonella quintana ; and we have described the Toscana virus, a major agent of meningitis and meningoencephalitis which was disseminated in North Africa and Central and Eastern Europe, where it frequently cocirculates with a large number of newly described phleboviruses transmitted by sand flies.